Removal of Reactive Blue 221 Dye from Textile Waste Water by Using Zinc Peroxide Nanoparticles (International Journal of Scientific Research and Management (IJSRM), 2017)
Zinc peroxide nanoparticles were synthesized by using ultrasound sonication process. Zinc peroxide nanoparticles was Characterized by X-ray diffraction, transmission electron microscope. Zinc peroxide nanopaticle are used as a catalyst for removal of a Reactive blue 221 dye. Maximum degradation efficiency of Reactive blue 221 dye was 85.52 % achieved by zinc peroxide with PEG as a catalyst and 81.69 % achieved by zinc peroxide without PEG as a catalyst at 120 min of photo catalytic reaction. The excellent degradation efficiency of Reactive blue 221 dye was achieved at the optimum operational conditions: initial concentration of dye 10 mg/lit, catalyst dosage of 200 mg, pH of solution will be in between 6.5 and temperature 35oC.